The field phenotyping platform's next darling: Dicotyledons - Li, Xiuni; Xu, Xiangyao; Chen, Menggen; Xu, Mei; Wang, Wenyan; Liu, Chunyan; Yu, Liang; Liu, Weiguo; Yang, Wenyu (Frontiers in Plant Science, 2022)
The genetic information and functional properties of crops have been further identified with the completion of whole-genome sequencing of numerous crops and the rapid development of high-throughput phenotyping technologies, laying a suitable foundation for advanced precision agriculture and enhance genetic gain. However, phenotypic acquisition of dicotyledonous crops in the field has been identified as a key factor in large-scale phenotypic acquisition of crops. On the one hand, dicotyledonous crops account for 4/5 of all angiosperm species and play a critical role in agriculture. On the other hand, their plant morphology is complex, and their phenotypic information is abundant, which is critical for the analysis of high-throughput phenotypic data in the field. As a result, the focus of this paper is on the major advancements in field phenotyping platforms on ground-based, air-based, and space-based platforms over the last few decades, as well as the research progress in high-throughput phenotyping of field dicotyledonous crops in morphological indicators, physiological and biochemical indicators, biotic/abiotic stress indicators, and yield indicators. Finally, we explored the future development of field dicotyledons from the perspectives of identifying unified new phenotypic criteria, developing a high-performance infrastructure platform, creating a phenotypic big data knowledge map, and merging with multiple omics.